Association of SUDOSCAN Values with Vibration Perception Threshold in Chinese Patients with Type 2 Diabetes Mellitus - Zhu, Xiaoming (Int J Endocrinol, 2017)
AIMS/INTRODUCTION: SUDOSCAN has been proved to be an efficient method in detecting diabetic microvascular complications. In this study, we determine to detect the possible relationship between vibration perception threshold (VPT) and cardiac autonomic neuropathy (CAN) values produced by SUDOSCAN. MATERIALS AND METHODS: A total of 920 Chinese patients with T2DM were enrolled in the study. Spearman correlation analysis and multivariate regression analysis were performed to determine the relation between CAN and VPT values. Mean VPT values across the CAN value tertiles were analyzed stratified by HbA1c status. RESULTS: In the study, we discovered a relatively high correlation between CAN value and both VPT values from dorsal feet and toes. Multivariate regression analyses also showed a significant relation between VPT and CAN values after adjusting all covariates. The mean value of VPT decreased across the SUDOSCAN-CAN value quartiles in both groups, and it was higher in patients with HbA1C > 9% than in patients with HbA1C < 9% across all quartiles of the SUDOSCAN-CAN except for the VPT mean in the low quartile of the SUDOSCAN-CAN value. CONCLUSIONS: All these results suggested that SUDOSCAN-CAN result was associated with VPT value which indicated a probable link between VPT value and cardiovascular autonomic dysfunction.